Caracterização da produção de banana (Musa spp.) por agricultores familiares nos municípios de Miracatu e Sete Barras e análise de perspectivas via matriz SWOT - Sejas, Rebeca Pardo (Universidade Federal de São Carlos, 2021)
Banana (Musa spp.) is one of the most important fruits in the world and is widely cultivated in tropical countries. In Brazil, after oranges, it represents the most important crop, not only for its high production volumes, but also for its consumption and commercialization. It is a culture that develops through social relations and family-type production which, depending on their geographic location, present several socioeconomic restrictions, mainly low education and deficient public policies, factors that make the process of commercialization and quality production difficult. Therefore, the objective of the research is to characterize banana production via family farming in the municipalities of Miracatu and Sete Barras and to analyze, through the SWOT matrix, perspectives for improvement for producers. For this, two types of questionnaires were used, one for farmers and another for cooperatives/associations. We interviewed 21 producers and two cooperatives in Sete Barras and 13 farmers, an association and a cooperative in Miracatu. With the information collected, it was possible to deduce that the organizations of the two municipalities were born driven by the Food Acquisition Program (PAA) and the National School Feeding Program (PNAE) of the Federal Government, with the objective of collaborating with the cooperative members in the production and banana marketing. Although these institutions have the same objective, the management philosophies were different, and Sete Barras has production initiatives with sustainability practices, while Miracatu has, as a priority, production in the conventional system. The cooperative members/associated with these organizations proved to be governed by the same system, since the farmers of Sete Barras presented a diversified culture in organic and agroforestry systems, while the producers of Miracatu mentioned that they are primarily dedicated to monoculture and conventional production.
Characterization of banana production (Musa spp.) by family farmers in the municipalities of Miracatu and Sete Barras and perspective analysis via SWOT matrix
Keywords: Produção de banana; Mercado de banana; Produtos processados; Agricultura familiar; Banana production; Banana market; Processed products; Family farming; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL